Criterios ambientales de cumplimiento para el desarrollo de proyectos de generación de energía marina en Costa Rica - Fallas-Madrigal, Mariana (Instituto Tecnológico de Costa Rica, 2018)
Global energy production projections place ocean energy as a renewable energy with a considerable growth potential in the next years. Ensuring that the deployment of innovative new technologies in the oceans does not compromise environmental sustainability is one of the defining challenges of ocean industrialization. This research suggests main environmental criteria that need to be addressed for marine energy development projects in Costa Rica. Such collection of criteria has been derived from an extensive literature review, oriented by international findings leading a criteria assessment matrix. Supported by an experts’ consultation process, results allowed environmental criteria prioritization process. Fisheries activities show a major urge in their assessment, followed by benthic ecosysems conservation actions. Relevant information was summarized into a guide, with the aim of providing decision-making criteria for developers and related regulatory authorities.
Proyecto Final de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2018.
Keywords: Energía; Planificación; Fuentes de energía renovable; Crecimiento; Nuevas tecnologías; Sostenibilidad ambiental